The Development of Public Finances and Role of Fiscal Constraints in a Monetary Union: Example eurozone - Jokinen, Niko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This thesis is about the development of public debt and deficit in the eurozone, which has been in the center of attention for much of the new millennium. The debt-to-GDP and deficit-to-GDP ratios have changed significantly during the period of the European monetary integration, with sharp increases in the levels since the beginning of the financial crisis. We view the levels both before and after the establishment of the European Central Bank. The subject is complemented by a study of the restrictions on fiscal policy in the eurozone. The thesis begins with a review of the most central agreements in the Economic and Monetary Union, namely the Maastricht Treaty, the Stability and Growth Pact and the Fiscal Compact. We study the instructions and requirements provided by these contracts, with the emphasis being on the debt and deficit values. Furthermore, we view two theories that aim to provide us with information, whether the fiscal restrictions are useful or not. The second and empirical part consists of review on the debt and deficit levels in practice. We take a close look on the values for each of the currency union members. The third and last part summarizes the findings, and analyzes the reasons behind the changes. The result of the thesis is, that even though the levels of public debt and deficit have worsened since the beginning of the financial crisis, tight rules on fiscal policy might not be the best possible solution. Private sector has played a crucial part in the increase of the debt levels, and tight rules have their impact on the long awaited economic growth in the eurozone. It is obvious, though, that some form of fiscal guidelines with scientific ground are needed in order to avoid excessive and harmful debt and deficit levels. The main task is to make these guidelines a more essential part of the fiscal policy in each of the member countries.